Assessing Models of Public-Private Partnership for Irrigation Development (AMPPPIDA): Findings from Ghana - International Food Policy Research Institute (2018)
AMPPPIDA presentation International Workshop on Assessing Models of Public-Private Partnership for Irrigation Development Mar 13, 2018 - 08:30 am to 02:00 pm GMT